The Effects of Ketapang (Terminalia catappa) Bark Crude Extract on Inhibition of Aeromonas hydrophila Growth and Blood Cells of the Infected Carp (Cyprinus carpio) - Maftuch, Maftuch; Suprastyani, Heny; Sanoesi, Ellana; Putra, Gede A. A. K.; Putra, Mirsa F.; Prihanto, Asep A. (Universitas Trunojoyo Madura, 2018)
The objectives of the research were to investigate the effect of ketapang (Terminalia catappa) bark crude extract (KBCE) on Aeromonas hydrophila growth and blood cells of the A. hydrophila-infected carp (Cyprinus carpio). The Research was conducted by using completely randomized design. There were four (750, 850, 950, and 1,050 ppm) and three treatments (730, 750, and 770 ppm) were used for in vitro and in vivo experiments respectively. Data were analyzed by analysis of variation and LSD. The dose to investigate MIC of KBCE were 750, 850, 950 and 1,050 ppm. The MIC of KBCE was 750 ppm. On in vivo investigation, number of erythrocytes were 224.67x10, 332.67x10, and 417.00x10 cells/mm for 730, 750 and 770 ppm KBCE, respectively. For leukocytes, the amount were 735.89x10, 684.78x10, and 652.67x10 cell/mm for 730, 750 and 770 ppm KBCE, respectively. In addition, the water quality were as follows 24.0 – 25.9C of temperature, 7.0 – 7.7 of pH, and 3.9 – 4.8 mg/L of DO. In conclusion, we revealed that KBCE able to act as antibacterial against A. hydrophila. Furthermore, it also induced the total erythrocyte in infected fish without giving a notable effect on water quality.